2015
DOI: 10.1002/hep.27578
|View full text |Cite
|
Sign up to set email alerts
|

Crucial roles of mixed‐lineage leukemia 3 and 4 as epigenetic switches of the hepatic circadian clock controlling bile acid homeostasis in mice

Abstract: The histone H3-lysine-4 methyltransferase mixed-lineage leukemia 3 (MLL3) and its closest homolog, MLL4 (aka KMT2D), belong to two homologous transcriptional coactivator complexes, named MLL3 and MLL4 complexes, respectively. MLL3 plays crucial roles in multiple metabolic processes. However, the physiological roles of MLL4 in metabolism and the relationship between MLL3 and MLL4 in metabolic gene regulation are unclear. To address these issues, we analyzed the phenotypes of newly generated MLL4 mutant mice, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 29 publications
2
55
0
Order By: Relevance
“…Previous studies demonstrated that the expression levels of Smad3, GATA4 and EGR1 were downregulated in the livers of MLL3-deficient mice, which was detected by RNA-seq and microarray (14,25). Furthermore, we found that H3K4me1 and H3K4me3 had multiple binding sites at the genomes of these three genes via analysis of the ChIPsequence data released in the ENCODE database.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Previous studies demonstrated that the expression levels of Smad3, GATA4 and EGR1 were downregulated in the livers of MLL3-deficient mice, which was detected by RNA-seq and microarray (14,25). Furthermore, we found that H3K4me1 and H3K4me3 had multiple binding sites at the genomes of these three genes via analysis of the ChIPsequence data released in the ENCODE database.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies have demonstrated that some HMTs are profoundly involved in the development of heart and cardiac remodeling (2,3,15 (14,25). As we have verified that MLL3 expression level was upregulated in the DCM hearts compared with donor hearts, we hypothesized that the expression levels of Smad3, GATA4 and EGR1 would increase in the hearts of DCM melanoma and pancreatic cancer (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 58%
“…Conditional knockouts of Mll2/Kmt2D with or without simultaneous knock-out of Mll3/Kmt2C revealed that Mll3/Kmt2C could partially compensate for loss of Mll2/Kmt2D in adipogenesis. A partial genetic redundancy between Mll3/Kmt2C and Mll2/Kmt2D was confirmed in a recent study comparing both single and compound Mll3/Kmt2C þ/-and Mll2/Kmt2D þ/-heterozygous deletion mice (123). Gene expression profiling in these mice revealed that both Mll3/Kmt2C and Mll2/Kmt2D were important for circadian-clock control and similar metabolic pathways in hepatic cells, including bile acid and lipid synthesis.…”
Section: Pathway Analysis Of Mll3/kmt2c and Mll2/ Kmt2d Deficiencymentioning
confidence: 75%
“…This increased NADH/NAD + ratio may relate to a previously described propensity of Kmt2d +/βGeo mice toward biochemical processes predicted to produce NADH, including beta-oxidation, and a resistance to high-fat-diet-induced obesity (27). If this exaggerated BHB elevation holds true in patients with KS, the KD may be a particularly effective treatment strategy for this patient population; however, this remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 92%